Jak szanuję to bez ale. SZACUNEK w wypowiedziach ankietowych lubelskich studentów - Gierczak, Sylwia Katarzyna (Vilnius University Open Series, 2021)
Celem artykułu jest przedstawienie wyników badań ankietowych dotyczących rozumienia pojęcia szacunku, zgodnie z ujęciem metodologicznym przyjętym w raporcie Język – wartości – polityka. Zmiany rozumienia nazw wartości w okresie transformacji ustrojowej w Polsce wydanym pod kierunkiem Jerzego Bartmińskiego (JWP 2006). W przeprowadzonym badaniu empirycznym posłużono się schematem lubelskiej ankiety ASA. Adekwatnie do przyjętej procedury wszystkim studentom obligatoryjnie zadano jedno pytanie: „Co – według Ciebie – stanowi o istocie prawdziwego szacunku?”.Do grupy respondentów włączono 100 studentów 5 lubelskich uczelni: Uniwersytetu Marii Curie -Skłodowskiej, Katolickiego Uniwersytetu Lubelskiego, Uniwersytetu Przyrodniczego, Uniwersytetu Medycznego i Politechniki Lubelskiej. W gronie ankietowanych byli przedstawiciele obu płci (kobiety i mężczyźni), wśród nich studiujący zarówno kierunki ścisłe, jak i humanistyczne.The data gathered from the students of Lublin universities point out to the profoundly social nature of ESTEEM – it was the social aspect (S) that had the most occurrences. On this level, the essence of esteem lies mainly in: 1) acceptance and empathy toward others (the trait most frequently mentioned by the respondents) – strongly linked to the respect for difference, tolerance, understanding and kindness, and thus clearly correlated with subjective treatment of other people; 2) courteous manners manifested through appropriate behaviour toward others (understood as positive treatment of others, proper wayof addressing people, or wearing occasion-appropriate attire), and appropriate treatment of animals and objects; 3) recognizing the other’s authority, clearly correlated with showing admiration/respect. The psychological (P), ethical (E) and psychosocial (A) aspects ranked second, third and fourth in the occurrence hierarchy, respectively. According to the respondents, the existential (B) and cultural (K) aspects are characterised by the lowest occurrence. The data gathered in the course of the survey is in agreement with the subjective denotation of the word szacunek, recorded in the primary position in all newer dictionaries of the Polish language: “recognition of the value of someone / something, consideration, regard”, or “particular regard or respect shown to someone / something”.
Keywords: semantyka; etnolingwistyka; aksjologia lingwistyczna; szacunek; ankieta